2022
DOI: 10.1116/6.0001596
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure plasma jet-mouse skin interaction: Mitigation of damages by liquid interface and gas flow control

Abstract: The possible benefits of an atmospheric pressure plasma jet skin treatment have been tested in vivo on mouse skin. Many studies have been conducted in vitro on mouse skin cells, but only a few in vivo where, due to the complexity of the biological system, plasma can cause severe damages. For this reason, we investigated how kHz plasma generated in a jet that is known to inflict skin damage interacts with mouse skin and explored how we can reduce the skin damage. First, the focus was on exploring plasma effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Therefore, they suggested that the electromagnetic radiation from the plasma could have a biological effect on cells. Additionally, Wu et al [125] once measured the magnetic field generated by the plasma jet using a magnetic field probe with a bandwidth ranging from 0.1 MHz to 1 GHz and found that the peak magnetic field produced by the plasma jet was approximately 0.05 dBm.…”
Section: Skin Resistormentioning
confidence: 99%
“…Therefore, they suggested that the electromagnetic radiation from the plasma could have a biological effect on cells. Additionally, Wu et al [125] once measured the magnetic field generated by the plasma jet using a magnetic field probe with a bandwidth ranging from 0.1 MHz to 1 GHz and found that the peak magnetic field produced by the plasma jet was approximately 0.05 dBm.…”
Section: Skin Resistormentioning
confidence: 99%
“…In fact, natural lightning processes contribute a substantial portion to global NF. Moreover, research on air plasma is related to various subjects such as atmospheric chemistry, [34] reentry heating of space vehicles, [35] surface treatment of materials, [36] plasma medicine, [37][38][39][40][41][42][43][44][45][46][47][48] and other plasma technologies. [49,50] In short, this paper will mainly focus on the progress of plasma NF using N 2 /O 2 mixture or dry air as the working gas.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, natural lightning processes contribute a substantial portion to global NF. Moreover, research on air plasma is related to various subjects such as atmospheric chemistry, [ 34 ] re‐entry heating of space vehicles, [ 35 ] surface treatment of materials, [ 36 ] plasma medicine, [ 37–48 ] and other plasma technologies. [ 49,50 ]…”
Section: Introductionmentioning
confidence: 99%
“…Figures 5(a) and 5(b) show the emission spectra in the 300-440 nm (exposure time = 1000 ms) and the 700-840 nm (exposure time = 20 ms) wavelength ranges, respectively.The emission spectra were minor in the 440-700 nm wavelength range. In experimental results suggesting that an unusual spectral change has an important effect on the change in liquid flows, the emission spectra were dominated by excited OH (309 nm), excited molecular N 2 (315-380 nm, 2nd positive system), and excited atomic Ar (around 420 nm, 700-840 nm) [27][28][29][30][31][32]. As the frequency increased from 4 to 10 kHz, the emission intensities of excited OH and excited molecular N 2 decreased while those of excited atomic Ar increased.…”
mentioning
confidence: 99%
“…In experimental results suggesting that an unusual spectral change has an important effect on the change in liquid flows, the emission spectra were dominated by excited OH (309 nm), excited molecular N 2 (315-380 nm, 2nd positive system), and excited atomic Ar (around 420 nm, 700-840 nm). [27][28][29][30][31][32] As the frequency increased from 4 to 10 kHz, the emission intensities of excited OH and excited molecular N 2 decreased while those of excited atomic Ar increased. Therefore, the plasma-driven liquid flows can be controlled by adjusting the active species supplied to the liquid surface.…”
mentioning
confidence: 99%